Handbook of radiotherapy physics theory and practice - Mayles, P.; Nahum, A.; Rosenwald, J.C (Taylor & Francis, 2007)
From background physics and biological models to imaging and treatment modalities, this book covers various theoretical and practical aspects of radiotherapy physics and biology. It discusses the support requirements of external beam radiotherapy and explores advances in photon and particle therapy. It offers a framework of radiation protection.